2007
DOI: 10.1152/ajpheart.01240.2006
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure attenuates muscle metaboreflex control of ventricular contractility during dynamic exercise

Abstract: DS. Heart failure attenuates muscle metaboreflex control of ventricular contractility during dynamic exercise. Am J Physiol Heart Circ Physiol 292: H2159 -H2166, 2007. First published December 22, 2006; doi:10.1152/ajpheart.01240.2006.-Underperfusion of active skeletal muscle elicits a reflex pressor response termed the muscle metaboreflex (MMR). In normal dogs during mild exercise, MMR activation causes large increases in cardiac output (CO) and mean arterial pressure (MAP); however, in heart failure (HF) alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 53 publications
7
50
0
1
Order By: Relevance
“…Steady-state data were recorded at rest, while the animal was standing on the treadmill, during exercise with unrestricted blood flow to the hindlimbs, and after metaboreflex activation elicited by reductions in HLBF achieved by partial inflation of the terminal aortic occluder, as previously described (49). After completion of the control experiments, modest congestive heart failure was induced via rapid ventricular pacing, as previously described by us and others (26,36). Briefly, the heart was paced at 240 -250 beats per minute (bpm) for ϳ30 days, and the experiments were repeated while in modest heart failure conditions [defined as resting tachycardia, reduced CO, SV, and left ventricular ϩ/ϪdP/dt, as described in our previous studies (8,14,36)].…”
Section: Methodsmentioning
confidence: 99%
“…Steady-state data were recorded at rest, while the animal was standing on the treadmill, during exercise with unrestricted blood flow to the hindlimbs, and after metaboreflex activation elicited by reductions in HLBF achieved by partial inflation of the terminal aortic occluder, as previously described (49). After completion of the control experiments, modest congestive heart failure was induced via rapid ventricular pacing, as previously described by us and others (26,36). Briefly, the heart was paced at 240 -250 beats per minute (bpm) for ϳ30 days, and the experiments were repeated while in modest heart failure conditions [defined as resting tachycardia, reduced CO, SV, and left ventricular ϩ/ϪdP/dt, as described in our previous studies (8,14,36)].…”
Section: Methodsmentioning
confidence: 99%
“…After all hemodynamic values had reached steady state, data were collected for ϳ 3-5 min. After completion of control experiments, modest congestive HF was induced via rapid ventricular pacing, a technique widely accepted to create a chronic model of ventricular failure (23,28). Briefly, the right ventricular pacing electrodes were connected to an external pacemaker set at 240 -250 beats/min for ϳ30 days.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the right ventricular pacing electrodes were connected to an external pacemaker set at 240 -250 beats/min for ϳ30 days. After an induction of modest HF (defined as resting tachycardia, reduced CO, SV, and maximum and minimum first derivative of left ventricular pressure) as described in our previous studies (8,9,14,28), the experiments were repeated. The pacemaker was turned off before each experiment, and data collection began after the hemodynamic variables had reached steady state (ϳ30 min).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the authors concluded that, in HF, the capacity of the muscle metaboreflex to increase the ventricular function through increases in contractility and filling pressure is evidently decreased 43 .…”
Section: Ergoreflex In Heart Failurementioning
confidence: 99%